ANALISIS KUALITAS BUTIR SOAL PENILAIAN AKHIR SEMESTER GASAL TAHUN 2021/2022 MENGGUNAKAN ITEMAN DI SMP NEGERI 1 KAMBERA - Marambaawang, Damianus; Bano, Vidriana Oktoviana; Hada Enda, Riwa Rambu (Dharmas Education Journal (DE_Journal), 2023)
In the data from the odd semester final exam results for the 2021/2022 school year, there are many students at SMPN 1 Kambera who score below the KKM standard. Referring to this, this study aims to evaluate the characteristics of each item of questions used in the final exam of the semester using several predetermined criteria. This study applies a quantitative descriptive method. The sample taken is class VIIID. The results of the analysis using ITEMAN show that 25% of the items are invalid and 75% of the items are valid. In addition, its reliability reaches a high level of "0.886". Based on the level of difficulty analysis, 17% of the questions were categorized as very easy, 14% were categorized as easy, and 15% were categorized as moderate. There were also 17% questions that were considered very difficult, and 37% questions that were considered difficult. Based on the cognitive level, there are 20 items that are included in the high difficulty level (HOTS) and 15 items that are included in the low difficulty level (LOWS). In terms of discriminating power, 88% of the items had good discriminating power, 3% of the items had poor discriminating power, and 9% of the items did not have good discriminating power. In research on distractor effectiveness, 54% of distractor choices were found to be effective, and 46% of distractor choices were ineffective.